THIN COCONUT COMMOMOGRAPHY FOR DETERMINATION OF HEARTIDINE IN ORANGE OF ORANGE FROM ORANGE - Sri Handayani; Sunarto Sunarto; Susila Kristianingrum (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
This research with the title Thin Layer Chromatography for Determination of Hesperidins Content in Orange Peel has been done in organic chemistry laboratory. The aim of this research is to select the solvent mix for the best hesperidins standard peak result and to determinate the content (in relative percentage) of some orange peel. Hesperidins isolation from orange peel conduct by soaks the orange peel piece in f 0% Calcium hydroxide solution for a night in room temperature. The mixture than jiltered and neutralized with hydrochloric acid to obtain hesperidins contain filtrate. Hesperidins analyzed by thin layer chromatography. Characterization of hesperidins did by compare the sample chromatogram with standard chromatogram. The yield (in relative percentage) determinate by compare the sample peak area with hesperidins standard peak area. The solvent mix selected before by attempt some solvent mix for eludate hesperidins standard solution. The result of this research shown that hesperidins can analyzed using thin layer chromatography method. with the best solvent was chloroform: methanol mixture (2 : 3). Hesperidins content in extract solution of some strain orange peel is; Baby Egypt 0, f 380%, Baby Pacitan 0,0615%, Mandarin Lokam 0,0018%, Santang 0,0049%, and Sunkist Nevel 0,0360%. The hesperidins content in orange peel of Mandarin Pakistan, Medan super, Nipis, Sunkist, Peras, and Purut was 0,0000. The hesperidins content in these orange peel was too low to be detected